The Legacy of unresolved loss a family systems approach - McGoldrick, Monica; Holland, John.; Newbridge Communications (New York, NY : Newbridge Communications, 1996)
Reenacts key moments in the 18-week course of therapy with a family in which the teenage daughter's rebellious behavior masks unresolved loss across three generations. In the course of her interactions with this family Dr. McGoldrick offers guidance in the use of genograms to assess patterns of unresolved loss, in assigning homework and rituals for helping families mourn, in evaluating the impact of factors such as ethnic and gender issues on a family's ability to cope with loss, and in supplementing regular family sessions with individual or couple sessions.
"A White Birch production."
Project editor and coordinating producer, Marge Lurie; executive producer, Lillian Schein; editorial consultants, Arthur Freeman, Leo Goldberger, Olga Silverstein; script, Donna Boundy; music by David Holland.
Melissa del Valle, Dan Strickler, Ty-Ranne Grimstad, Patrick Horrigan.
Mental health professionals.
VHS format.
Keywords: Family psychotherapy; Grief therapy; Bereavement; Family psychotherapy -- Methods; Systems Theory; Families -- Health and hygiene; Families -- Psychological aspects; Grief